Chapter Introduction - Szreter, Simon (University of Rochester Press, 2019)
This volume is a necessarily multidisciplinary collection dedicated to the extremely difficult task of uncovering and exploring what can be reconstructed of the dimensions and the scale of the historical impact of sexually transmitted infections (STIs) on human infertility. As a subject for inquiry, this comes close to Winston Churchill's celebrated phrase, "a riddle, wrapped in a mystery, inside an enigma."